Effectiveness of the 5E Learning Cycle Model in Vocational Pharmaceutical Chemistry Learning: A Review - Dwi Putri Rejeki; Fita Nelyza; Irma Zarwinda; Eva Novita (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study is a systematic literature review aimed at analyzing the effectiveness of the Learning Cycle 5E instructional model in enhancing students’ conceptual understanding and scientific attitudes, while also examining its potential application in Pharmaceutical Chemistry learning at the vocational higher education level. This review addresses the growing need for active learning models that can bridge conceptual understanding with the practical competency demands of pharmaceutical education. The analysis employed a narrative synthesis approach, reviewing relevant research articles based on four main dimensions: learning context, research focus, research methodology, and reported key findings. The results indicate that the Learning Cycle 5E model consistently improves students’ conceptual understanding, reduces misconceptions, and fosters the development of scientific attitudes such as curiosity, responsibility, openness to evidence, and reflective thinking. In addition, several studies report that integrating the Learning Cycle 5E model with interactive learning technologies, including digital media and student-centered learning tools, enhances student motivation and active engagement in the learning process. Although most of the reviewed studies are situated within general chemistry education, the findings demonstrate strong relevance and high potential for application in Pharmaceutical Chemistry learning contexts. Therefore, this review recommends further implementation-based research in vocational higher education to strengthen empirical evidence and optimize the design of active, contextual, and reflective pharmaceutical learning.